Mechanical Properties, Failure Mode, and Microstructure of Soil-Cement Modified with Fly Ash and Polypropylene Fiber - Xue-lei Duan; Jing-shuang Zhang (Advances in Materials Science and Engineering)
In order to investigate the effects of fly ash and polypropylene fiber on mechanical properties, failure mode, and microstructure of soil-cement, the unconfined compression test, splitting tension test, and scanning electron microscopy (SEM) test of soil-cement with different polypropylene fiber contents (0%, 0.1%, 0.2%, 0.3%, 0.4%, and 0.5% by weight of dry soil) and fly ash contents (0%, 4%, 8%, and 12% by weight of dry soil) were carried out. The compressive and tensile strengths, deformation characteristics, failure mode, and microstructure of soil-cement modified with fly ash and polypropylene fiber were analyzed. The results show that the unconfined compressive strength and splitting tensile strength of soil-cement show a trend of increasing first and then decreasing with the increase of polypropylene fiber and fly ash content. Under the condition of 0.4% polypropylene fiber and 8% fly ash, the unconfined compressive strength and the splitting tensile strength are 4.90 MPa and 0.91 MPa, respectively, which increased by 32.79% and 51.67% as compared with the plain soil-cement, respectively. When 8% fly ash was used in the experiment, the unconfined compressive peak strain and the splitting tensile peak strain of the inclusion of 0.4% polypropylene fiber were 0.0410 and 0.0196, respectively. The corresponding peak strains were increased by 20.94% and 68.97% as compared with non-fiber-stabilized soil-cement, respectively. The stress-strain curve of fly ash soil-cement modified with polypropylene fiber can be divided into compaction phase, linear rise phase, nonlinear rise phase, and failure phase. Polypropylene fiber constrains the lateral deformation of fly ash soil-cement, which improves the peak strain and the failure mode of soil-cement.